2006
DOI: 10.1248/bpb.29.172
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Helicobacter pylori Motility by (+)-Syringaresinol from Unripe Japanese Apricot

Abstract: Helicobacter pylori was isolated from the gastric antrum of chronic gastritis patients. H. pylori is closely associated with gastritis and peptic ulcers and is even a bacterial risk factor for gastric cancer.1-4) Therefore, eradication of the bacteria and inhibition of the urease are important for the treatment of patients with gastroduodenal diseases.The standard treatment for H. pylori related disease is a combination of antimicrobial agents and anti-acid agent. 5)However, the drug resistant H. pylori agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(49 citation statements)
references
References 14 publications
1
43
0
3
Order By: Relevance
“…However, Miyazawa et al (2006) report that ( þ )-syringaresinol, a lignan contained in JA extract, inhibits H. pylori motility. In addition, Fujita et al (2002) found that JA extract has direct bactericidal activity against H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…However, Miyazawa et al (2006) report that ( þ )-syringaresinol, a lignan contained in JA extract, inhibits H. pylori motility. In addition, Fujita et al (2002) found that JA extract has direct bactericidal activity against H. pylori.…”
Section: Discussionmentioning
confidence: 99%
“…From ancient times, various parts of P. mume have been used as a health food and a medicinal agent for the treatment of fever, cough, and intestinal disorders. In addition, recent studies have reported that P. mume possesses various pharmacological activities, including inhibition of influenza A virus and motility of Helicobacter pylori, potential sources of free radical scavengers, improvement of blood fluidity, anti-inflammation, and anti-cancer action (21)(22)(23)(24)(25)(26)(27)(28). However, the cellular and molecular mechanisms responsible for the apoptotic effects of P. mume have not yet been determined in human cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that P. mume exerts a wide array of pharmacological and biological activities, such as potential sources of free radical scavengers, inhibition of influenza A virus, inhibition of the motility of Helicobacter pylori, improvement of blood fluidity, and inhibition of pro-inflammatory mediators (20)(21)(22)(23)(24)(25). In addition, P. mume has been known to exert anticancer activities in several types of human cancer cells (26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…혈구암은 임상 및 병리학적으로 급성 및 만성 혈구암으로 구분되어지는데 급성 혈구암의 경우에는 어린이나 젊은 층에서 주로 발병하지 만 만성 혈구암의 경우에는 나이가 많은 사람에게 주로 발병 하는 것으로 알려져 있다. 또한 혈구암은 골수에 위치하는 림 프구에서 유발되는 급성 림프구성 백혈병(acute lymphocytic leukemia)과 과립성 백혈구 및 단핵 백혈구에서 유발되는 골 수성 백혈병(myelogenous leukemia)으로 구분되어 진다 [1,15] [5,6,23,34,51]. 또한 매실은 많은 인체 암세포에 있어서 항암활 성을 가지는 것으로 보고되어지고 있으나 [35,36,38] [31].…”
Section: 서 론unclassified
“…또한 매실은 많은 인체 암세포에 있어서 항암활 성을 가지는 것으로 보고되어지고 있으나 [35,36,38] [31]. 최근 매실 추출물의 다양한 약리 효과가 보고되어져 오고 있으나 [5,6,23,[34][35][36]38,51] …”
Section: 서 론unclassified